AZOLLA SUPPLEMENTATION: FEED COST BENEFIT IN DUCK RATION IN ANDAMAN ISLANDS - T. Sujatha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A 13 weeks experiment was conducted to study the production  performance and feed cost benefit with fresh Azolla supplementation in the feed of native local ducks. Forty indiscriptive local ducks of 20 weeks age were randomly divided into two groups with two replicates of each. Two replicates were assigned to each of the two dietary treatments in a completely randomized design, in such a manner that standard layer mash (control group) and commercial Layer mash + 200 gm fresh Azolla (Azolla group). The feed consumption was considerably low with Azolla supplementation as against control group. Results revealed that there was no significant difference in egg productivity between Azolla supplemented and control group. A significant amount of 30 per cent feed savings lead to reduced feed cost. Egg weight and other quality parameters were similar to control group. However, Roche fan colour score increased with Azolla supplementation in the die.